A Study on Residential Architecture and Life Quality of the Elderly in Northern Iraq - Faqra, Avy Nazar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
As it is known for the whole world, getting old is a period of life cycle of the human beings, just like their previous ones. But what should be known is that it is a special phase of life and needs to be treated accordingly. Since forever, housing conditions have been directly affecting older people’s quality of living and been making them decide their decisions accordingly. Within this regard, at this stage of life, the quality of the living environment is the most important aspect of their lives as it directly affects them, due to its surrounding them in every way. Within this regard determining those aspects that affects quality of the living of those elderly needs to be taken into consideration in every part of the world, whether the country is a developed one or newly developing. Within this context, the main aim of this study is to determine the level of residential satisfaction of the elderly aged more than 60 years old in Northern Iraq and how the quality of life is affected by it. The study begins by creating a theoretical background between the phrases such as quality of life, residential environment and elderly based on the residential satisfaction as a main context of the study. After that, a review of literature about those previously conducted studies about quality of life and residential satisfaction is done. It provides an image about how those previously made studies have been evaluated, measured and concluded. In order to provide a clear perception about their participant’s assessment of their surroundings and their levels of satisfaction. Accordingly, the domains of residential satisfaction are explained which are house and neighborhood. With their roles as variables that predict and describe residential satisfaction. In order to reach the aim of the research a mixed methodology approach have been used consisting of qualitative and quantitative methods. The quantitative data have been gathered through a survey questionnaire among a sample size of 384 elderly living in Sulaimanyah city in Northern Iraq. With qualitative data being gathered through semi- structured interviews with 36 elderly and observation with physical analysis of 30 houses within Sulaimanyah. Based on the findings of the study, the levels of residential satisfaction are determined and housing conditions of the elderly are described. With determining the main factors that affects residential satisfaction of the elderly in Northern Iraq, the results are discussed and compared. Keywords: Elderly, Quality of Life, Residential Environment, Residential Satisfaction

ÖZ: Tüm dünyanın bildiği üzere yaşlanmak insanoğlunun diğer aşamalarda olduğu gibi yaşam döngüsünün bir parçasıdır. Fakat, bilinmelidir ki bu yaşamın önemli bir aşamasıdır ve ona göre davranılması gerekmektedir. En başından beri konut tasarımımı ve koşulları yaşlıların yaşam kalitesini doğrudan etkilemekte ve kararlarını ona göre almalarını sağlamaktadır. Bu bakımdan hayatlarının bu aşamasında, yaşam kalitesi onları doğrudan etkileyen en önemli unsurların başında gelmektedir. Bu bağlamda ülkenin gelişmiş veya yeni gelişmekte olmasına bakılmaksızın, yaşlıların yaşam kalitesini etkileyen konuların irdelenmesi dünyanın her yerinde dikkate alınmaktadır. Bu çalışmanın esas amacı Kuzey Irak, Süleymaniye şehrinde yaşayan 60 yaş üzeri yaşlıların konut memnuniyet seviyesini ölçüp, hayat kalitelerinin bundan nasıl etkilendiğini tespit etmektir. Çalışma, öncelikle, yaşam kalitesi, konut tasarımı ve yaşlıların konut memnuniyeti kavramları ile ilgili teorik bir arka plan oluşturarak başlamıştır. Buna paralel olrak, yaşam kalitesi ve konut memnuniyeti konularında yapılmış bilimsel çalışmalar taranıp konu ile ilgili olarak sunulmuştur. Bununla birlikte, daha önce yapılan çalışmalarda hangi değerlendirme tekniklerinin kullanıldığı, nasıl ölçüldüğü ve sonuçlandığı hakkında bilgi verip, başlıca değerlendirme kriterleri belirtilmiştir. Özellikle, konut memnuniyetinin etki alanını oluşturan konut tasarımı ve çevresi konuları tartışılıp, konut memnuniyetindeki başlıca rolleri açıklanmıştır. Araştırmanın amacına ulaşmak için kalitatif ve kantitatif yöntemlerin oluşturduğu karma bir araştırma metodu kullanılmıştır. Kantitatif veri Kuzey Irak’ın Süleymaniye şehrinde yaşayan 384 yaşlı ile yapılan anket çalışmasından toplanmıştır. Kalitatif veri ise 36 yaşlı ile yapılan yarı yapılandırılmış görüşme ve Süleymaniye’de 30 evde yapılan fiziksel analiz yöntemi ile toplanmıştır. Çalışmanın bulgularına dayanarak, konut memnuniyetinin seviyesi kararlaştırılmış ve yaşlıların konut tasarımı ve koşulları anlatılmıştır. Kuzey Irak’ın Süleymaniye şehrinde yaşayan 60 yaş üzeri yaşlıların konut memnuniyetini etkileyen esas faktörler kararlaştırılarak, sonuçlar tartışılmış ve karşılaştırılmıştır. Anahtar kelimeler: Yaşlı, Yaşam Kalitesi, Konut Mimarisi, Konut Memnuniyeti.
Master of Science in Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2020. Supervisor: Asst. Prof. Dr. Nazife Özay.
Keywords: Architecture; Domestic architecture; Residential and related buildings; Elderly; Quality of Life; Residential Environment; Residential Satisfaction